2012
DOI: 10.1115/1.4007591
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experimental Validation of a Ducted Counter-Rotating Axial-Flow Fans System

Abstract: An experimental study on the design of counter-rotating axial-flow fans was carried out. The fans were designed using an inverse method. In particular, the system is designed to have a pure axial discharge flow. The counter-rotating fans operate in a ducted-flow configuration and the overall performances are measured in a normalized test bench. The rotation rate of each fan is independently controlled. The relative axial spacing between fans can vary from 17% to 310%. The results show that the efficiency is st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…In addition, a larger axial gap results in improvement in acoustic performance while degrading the aerodynamic performance, and the peak pressure point occurring at a lower flow rate. However, the study reported by Nouri et al 17,18 for axial gap changes from 10 to 50 mm indicates no obvious change in overall performance.…”
Section: Introductionmentioning
confidence: 74%
“…In addition, a larger axial gap results in improvement in acoustic performance while degrading the aerodynamic performance, and the peak pressure point occurring at a lower flow rate. However, the study reported by Nouri et al 17,18 for axial gap changes from 10 to 50 mm indicates no obvious change in overall performance.…”
Section: Introductionmentioning
confidence: 74%
“…Contra-rotating rotors have been adopted for some of the high power cooling fans to meet the demand for high power. On the other hand, low rotational speed design [5] and advantages on the performance of the contra-rotating fans and pumps were verified by experimental results [6]- [8]. The company's research and development period for the contra-rotating small-sized cooling fan was short and its internal flow condition was not clarified well.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, the contra-rotating rotors are adopted for the small-sized axial fans to increase the performance. The lower rotational speed design [1] and advantages on the performance of the contra-rotating fans and pumps were verified by experimental results [2] [3]. In the case of contra-rotating rotors, the axial space becomes larger than conventional small-sized axial fans.…”
Section: Introductionmentioning
confidence: 99%